Position and implementation of educational programs in modern school - Stamatović Jelena D.; Milošević Aleksandra M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
One of the critiques of modern school is to emphasize the development of cognitive components of pupils, while paying less attention to the development of other components of pupils. It is therefore important to develop quality educational programs in schools that should contribute to pupil development. The aim of the paper is to examine the existence, position and realization of educational programs in elementary and secondary schools in Zlatibor district. Using the analysis of annual program documentation and school performance reports, the categories of program elements are analyzed: objectives, thematic structure and modes of realization. The results show that in schools, there are generally declarative programs (work programs of homeroom teacher, professional orientation programs, health programs, ecological programs, violence prevention programs and work programs of the pupil parliament). These programs only contain a thematic structure in which there is very little perceived differentiation in relation to the school level (primary, secondary), as well as in relation to the age of pupils within the elementary school and in relation to needs, taking into account the circumstances in which schools work (school environment, school size...). Given this situation, it is clear that the strategies for creating educational programs must be planned more seriously, starting from the needs of a particular school, taking into account the abilities and development of pupils' potential in school.